2018
DOI: 10.1111/1365-2656.12895
|View full text |Cite
|
Sign up to set email alerts
|

A mimicked bacterial infection prolongs stopover duration in songbirds—but more pronounced in short‐ than long‐distance migrants

Abstract: Migration usually consists of intermittent travel and stopovers, the latter being crucially important for individuals to recover and refuel to successfully complete migration. Quantifying how sickness behaviours influence stopovers is crucial for our understanding of migration ecology and how diseases spread. However, little is known about infections in songbirds, which constitute the majority of avian migrants. We experimentally immune-challenged autumn migrating passerines (both short- and long-distance migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
(122 reference statements)
0
29
0
Order By: Relevance
“…viruses, bacteria), we can, however, not exclude that additional co-infections may contribute to the observed effects. In any case, free-flying birds undergoing infections might not only prolong stopover duration (Hegemann et al 2018 , this study), but pathological sickness symptoms may also reduce their flight range. Interestingly, birds infected with blood parasites showed significantly longer landscape movements (i.e., movements away from the catching site) than uninfected birds and there was a trend that this effect increased from single to double infections.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…viruses, bacteria), we can, however, not exclude that additional co-infections may contribute to the observed effects. In any case, free-flying birds undergoing infections might not only prolong stopover duration (Hegemann et al 2018 , this study), but pathological sickness symptoms may also reduce their flight range. Interestingly, birds infected with blood parasites showed significantly longer landscape movements (i.e., movements away from the catching site) than uninfected birds and there was a trend that this effect increased from single to double infections.…”
Section: Discussionmentioning
confidence: 84%
“…First, in passerine birds, haptoglobin concentrations in the range of 1.0–2.0 mg/ml or even higher regularly occur (Hegemann et al 2012a ; Vermeulen et al 2016 ; Ndithia et al 2017 ; Fowler and Williams 2017 ). Second, haptoglobin concentrations increase during inflammation (Thomas 2000 ; Buehler et al 2009 ; Matson et al 2012 ; Hegemann et al 2013a ; but see Schultz et al 2017 ) and third, a recent study has shown that birds prolong their stopover duration during an experimentally induced inflammatory response (Hegemann et al 2018 ). That we had only one bird in our dataset with very high haptoglobin values is not surprising, because this is a marker of an on-going acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hegemann et al (2015) hypothesised that individuals which are sick or parasitized need to invest into an acute immune response. Such a response includes a range of energetically, physiologically and behaviourally costly adjustments (Lee et al 2005;Owen-Ashley et al 2006;Owen-Ashley and Wingfield 2007;Hegemann et al 2012bHegemann et al , 2013aHegemann et al , 2018Sköld-Chiriac et al 2015). Consequently, infected individuals might not be able to afford a demanding migration and hence have to become resident.…”
Section: Immune Systemmentioning
confidence: 99%
“…Thus, parasite dispersal and/or the accumulation of new infections along migratory routes is typically seen as a consequence of migratory behaviour rather than parasites themselves acting as drivers of host migration decisions (Altizer, Bartel, & Han, 2011). Yet, theoretical and empirical evidence that parasites influence the migratory decisions of their hosts is increasing (Daversa, Fenton, Dell, Garner, & Manica, 2017; Daversa, Manica, Bosch, Jolles, & Garner, 2018; Halttunen et al, 2018; Hegemann et al, 2018; Shaw & Binning, 2016; Shaw, Craft, Zuk, & Binning, 2019b). Predicting how infection may influence host migration requires not only accounting for changing infection risk, but also being explicit about the mechanism linking infection and migration—infection could be predicted to either increase or decrease host migration depending on the circumstance (Binning, Shaw, & Roche, 2017).…”
Section: Introductionmentioning
confidence: 99%